The synergistic effect of insomnia and depression on risk of herpes zoster - Wu, Hsueh-Ching; Lin, Chia-Ling; Chung, Chi-Hsiang; Chien, Wu-Chien (Journal of neurovirology, 2024)
Sleep problems was associated with increased risk for herpes zoster (HZ). This study examined subjects with insomnia or a combination of insomnia and depression and their risk of HZ. This retrospective cohort study included a total of 47,256 participants, with a control comprising 31,504 age- and sex-matched patients. Clinical data from 2000 to 2013 in the Taiwan National Health Insurance Research Database were used for analysis. Insomnia, depression, and HZ were defined according to the International Classification of Diseases, Ninth Revision, Clinical Modification. Subjects with insomnia had a significantly higher incidence of HZ (2.77 per 1000 person-years) than the controls (1.81 per 1000 person-years) as well as a higher risk of developing HZ (adjusted hazard ratio (AHR) = 1.62, 95% confidence interval (CI) = 1.35–1.93). Results shown subjects with insomnia durations of < 4 years, 4–6 years, and > 6 years had a significantly higher risk of HZ compared with the controls (AHR: 6.69, 95% CI 4.44–9.39; AHR: 4.42, 95% CI 3.07–6.36; AHR:1.38, 95% CI 1.14–1.87, respectively). We found a significantly higher risk of HZ in subjects with both insomnia and depression (AHR = 4.95; 95% CI = 3.99–7.02) than in those without related conditions. Patients with insomnia, and even more so those with comorbid depression, had a higher risk of developing HZ. This indicates a joint effect of insomnia and depression on HZ.